Modeling and Analysis of Time Response Parameters of a PMSM-Based Electric Vehicle with PI and PID Controllers - Yerri Veeresh, M.; Bhaskar Reddy, V. N.; Kiranmayi, R. (Engineering, Technology & Applied Science Research, 2022)
This paper presents the mathematical modeling of a vector-controlled Permanent Magnet Synchronous Motor (PMSM) drive with either a Proportional Integral (PI) controller or a Proportional Integral Derivative (PID) controller as a propulsion system for an Electric Vehicle (EV). Most commercial drives use a standard PI controller as a speed regulator. The vector control system model consists of the PMSM, a PWM inverter, the speed controller, and vehicle dynamics for speed control. The performance analysis of the drive is evaluated under transient conditions for settling time, rise time, steady state error of speed, and the vehicle’s acceleration at the wheel axle for specifically designated values validated by MATLAB/Simulink.